Additive for lithium ion secondary battery positive electrode material, lithium ion secondary battery positive electrode material, and method for producing additive for lithium ion secondary battery positive electrode material

A composite oxide additive with specific elements and composition enhances the crystallinity of lithium ion secondary battery positive electrode materials, addressing the issue of insufficient crystal structure development and improving battery performance.

JP2025005862APending Publication Date: 2025-01-17NIPPON DENKO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023106270
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

Smart Images

  • Figure 2025005862000001
    Figure 2025005862000001
Patent Text Reader

Abstract

To provide an additive for a lithium ion secondary battery positive electrode material, which promotes crystal growth during positive electrode material synthesis.SOLUTION: An additive for a lithium ion secondary battery positive electrode material of the present invention is an additive which is added in a process where a precursor of a lithium ion secondary battery positive electrode material is reacted with a lithium salt to prepare a positive electrode material, the additive comprising a composite oxide. The compositional formula of the composite oxide is MxZr1-xO2-y, where M represents one or more elements selected from among La, Sc, Sm, Nd, Gd, Yb and Y, x is in a range of 0<x<1, and y is in a range of 0<y<1.5. In an X-ray diffraction of the composite oxide using CuKα as a ray source, a half band width of a diffraction peak appearing at 2θ=30±1° is 1° or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an additive for a positive electrode material of a lithium ion secondary battery, a positive electrode material for a lithium ion secondary battery, and a method for producing the same. [Background technology]

[0002] Lithium-ion secondary batteries are widely used as batteries for electronic devices and communication devices. Among them, positive electrode materials (positive electrode active materials) with a layered structure have a large capacity and are therefore used in vehicles and power storage equipment. One of the technologies to improve the performance of lithium-ion secondary batteries is the use of additives (composite oxides) to the positive electrode active material.

[0003] Patent Document 1 discloses a positive electrode material for a lithium ion secondary battery. According to Patent Document 1, a positive electrode material having a layered crystal structure in which the lithium layers are spaced apart is extremely effective in improving output characteristics by substituting a cation B, which has an ionic radius larger than that of lithium ions and has a valence of 2 or more, for lithium ions between the layers of the positive electrode material having a layered crystal structure, and the use of a composite oxide of cations A and B as an additive thereto is disclosed.

[0004] Patent Document 2 discloses a positive electrode material for a lithium ion secondary battery. According to Patent Document 2, when the particle diameter of the secondary particles of a positive electrode material for a lithium ion secondary battery having a layered crystal structure is two to five times the crystallite size, almost all of the crystals constituting the secondary particles appear on the secondary particle surface, facilitating the insertion and removal of lithium ions, and it is said that in a method for producing a positive electrode material having a layered structure by reacting a precursor not containing lithium with a lithium salt, a positive electrode material having excellent properties can be produced without using an excess of lithium salt.

[0005] In Patent Document 3, Li a Ni x Mn y Co z M w O 2-t At According to Patent Document 3, a positive electrode active material represented by the formula: is characterized in that a metal cation represented by M having an ionic radius larger than that of Ni cation is contained in the Li cation site or in the vacant space in the crystal lattice so as to prevent mixing of Ni cations in the Li layer, and it is said that the performance of a lithium ion secondary battery containing the positive electrode active material is improved.

[0006] Patent Document 4 discloses a method for producing a positive electrode material for lithium secondary batteries. Patent Document 4b discloses a positive electrode material represented by LiMO2, which contains a metal element M other than Li that has an ionic radius equal to or greater than that of Li, and according to Patent Document 4, by reliably inserting M between the Li layers, M functions as a pillar that maintains the matrix skeleton, thereby preventing phase change, and thus a lithium metal oxide having a discharge capacity higher than the value known as the theoretical discharge capacity of a lithium ion secondary battery can be obtained.

[0007] Patent Document 5 discloses a positive electrode active material. According to Patent Document 5, the positive electrode active material includes lithium transition metal oxide particles and composite particles, the composite particles including any one selected from the group consisting of YSZ, GDC, LSGM, LSM, and Ni-YSZ, or a mixture of two or more of these, and the positive electrode active material has composite particles with a single phase peak when measured by X-ray diffraction (XRD), and is said to be capable of minimizing the capacity reduction and output reduction of a secondary battery as well as further improving the life characteristics.

[0008] Patent Document 6 discloses a positive electrode active material for lithium secondary batteries. According to Patent Document 6, a lithium cobalt composite oxide containing Sr atoms and Ti atoms is produced by firing a mixture containing strontium titanate, so that Sr atoms are present both inside and on the particle surface of the lithium cobalt composite oxide particles, resulting in a high packing density. Also, a lithium secondary battery using the lithium cobalt composite oxide as a positive electrode active material has a high capacity per volume and is excellent in safety, cycle characteristics, and operating voltage.

[0009] Patent Document 7 discloses a method for producing a positive electrode material for a non-aqueous secondary battery. According to Patent Document 7, a lithium transition metal composite oxide obtained by mixing a lithium-containing compound, a nickel-containing compound, and BaTiO3 and baking the mixture contains titanium in a solid solution throughout the particles, which can control the reduction of nickel, thereby enabling the realization of a non-aqueous secondary battery that generates little gas during high-temperature storage.

[0010] Patent Document 8 discloses a positive electrode active material for a lithium ion secondary battery. The positive electrode active material disclosed in Patent Document 8 is represented by the general formula Li z Ni 1-x-y Co x M y The lithium metal composite oxide powder is represented by the formula (x, y, z), and is represented by the formula (x, y, z). The formula (x, y, z) is 0.01≦x≦0.35, 0≦y≦0.35, 0.97≦z≦1.20, and M is an additive element and is at least one element selected from Mn, V, Mg, Mo, Nb, Ti, and Al. The lithium metal composite oxide powder is composed of primary particles and secondary particles formed by agglomeration of the primary particles, and includes a mixture of lithium lanthanum zirconate.

[0011] Patent Document 9 discloses a positive electrode material for non-aqueous electrolyte secondary batteries. The positive electrode active material disclosed in Patent Document 9 includes a lithium transition metal composite oxide having a layered crystal structure containing at least lithium and nickel as a core particle, and a coating layer composed of a composite oxide containing lithium, yttrium, and zirconium is formed on at least a part of the surface of the core particle. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2020-167014 A [Patent Document 2] JP 2021-163560 A [Patent Document 3] Special Publication No. 2015-503181 [Patent Document 4] Japanese Patent Application Publication No. 11-354121 [Patent Document 5] Special Publication No. 2016-506032 [Patent Document 6] JP 2013-182757 A [Patent Document 7] JP 2019-114454 A [Patent Document 8] JP 2018-055808 A [Patent Document 9] JP 2018-073563 A Summary of the Invention [Problem to be solved by the invention]

[0013] In order for a lithium transition metal composite oxide having a layered structure to fully exhibit its capabilities as a positive electrode material for a lithium ion secondary battery, it is desirable that the crystal structure is fully developed. However, in general, even if an additive is added to synthesize a positive electrode material, the crystal structure does not fully develop. The present invention has been made in consideration of the above problems, and an object of the present invention is to provide an additive for a positive electrode material for a lithium ion secondary battery that promotes crystal growth during synthesis of the positive electrode material. Here, whether or not an additive for a positive electrode material for a lithium ion secondary battery promotes crystal growth during synthesis of the positive electrode material can be determined by the half-width of an X-ray diffraction peak that appears around 2θ=18 to 20° in X-ray diffraction of the manufactured positive electrode material for a lithium ion secondary battery using a CuKα radiation source. In the present invention, if the half-width of the X-ray diffraction peak is 0.223° or less, it is determined that crystal growth is promoted during synthesis of the positive electrode material. [Means for solving the problem]

[0014] The inventors of the present invention have conducted intensive studies to solve the above problems. As a result, they have found that by controlling the half-value width of the diffraction peak in X-ray diffraction of the additive added to the positive electrode material, the crystal growth of the positive electrode material can be promoted and the characteristics of the positive electrode material can be improved. The present invention has been further studied based on the above findings, and the gist thereof is as follows.

[0015] [1] An additive composed of a composite oxide added in the step of producing a positive electrode material by reacting a precursor of a lithium ion secondary battery positive electrode material with a lithium salt, wherein the composition formula of the composite oxide is M x Zr 1-x O 2-y where M is one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y, satisfying 0 < x < 1 and 0 < y < 1.5, and in the X-ray diffraction of the composite oxide with a CuKα radiation source, the half-value width of the diffraction peak appearing at 2θ = 30 ± 1° is 1° or more. An additive for a lithium ion secondary battery positive electrode material.

[0016] [2] The additive for a lithium ion secondary battery positive electrode material according to [1] above, characterized in that the specific surface area is 50 m 2 / g or more.

[0017] [3] The additive for a lithium ion secondary battery positive electrode material according to [1] or [2] above, characterized in that M is any one or more elements selected from Gd, Y, and Sc.

[0018] [4] The additive for a lithium ion secondary battery positive electrode material according to [1] or [2] above, characterized in that M is two or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y.

[0019] [5] A lithium ion secondary battery positive electrode material using the additive for a lithium ion secondary battery positive electrode material according to any one of [1] to [4], characterized in that in the X-ray diffraction with a CuKα radiation source, the half-value width of the X-ray diffraction peak appearing in the vicinity of 2θ = 18 to 20° is 0.223° or less.

[0020] [6] A lithium ion secondary battery positive electrode material using two or more kinds of the additives for a lithium ion secondary battery positive electrode material according to any one of [1] to [4] above, wherein the half width of an X-ray diffraction peak appearing in the vicinity of 2θ=18 to 20° in X-ray diffraction using a CuKα radiation source is 0.223° or less.

[0021] [7] A method for producing the additive for a positive electrode material of a lithium ion secondary battery according to any one of [1] to [4] above, comprising a step of calcining a powder of a composite oxide raw material of the additive for a positive electrode material of a lithium ion secondary battery at 400° C. or more and 800° C. or less.

[0022] [8] The method for producing an additive for a positive electrode material of a lithium ion secondary battery according to [7] above, wherein the powder, which is a raw material of a composite oxide of an additive for a positive electrode material of a lithium ion secondary battery, is produced by a method including the steps of: (1) dissolving a raw material of a composite oxide of an additive for a positive electrode material of a lithium ion secondary battery in water to prepare a raw material aqueous solution; (2) precipitating a precipitate from the raw material aqueous solution; (3) maturing a solution containing the precipitate; (4) washing the precipitate; and (5) drying the precipitate. Effect of the Invention

[0023] According to the present invention, it is possible to provide an additive for a positive electrode material of a lithium ion secondary battery that promotes crystal growth during synthesis of the positive electrode material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Additives for cathode materials in lithium-ion secondary batteries The additive for a positive electrode material of a lithium ion secondary battery of the present invention will be described below.

[0025] The additive for the positive electrode material of the lithium ion secondary battery of the present invention (hereinafter, also simply referred to as "additive") is used in the production of the positive electrode material of the lithium ion secondary battery (hereinafter, also simply referred to as "positive electrode material"). More specifically, it is added in the step of reacting the precursor of the positive electrode material with a lithium salt to produce a positive electrode material having a layered structure. The additive has a composition formula of M x Zr 1-x O 2-y and is composed of a composite oxide represented by. Here, M is one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y, x is in the range of 0 < x < 1, and y is in the range of 0 < y < 1.5. Further, in the X-ray diffraction of the composite oxide with a CuKα ray source, the half-value width of the diffraction peak appearing at 2θ = 30 ± 1° is 1° or more.

[0026] The positive electrode material having a layered structure is a positive electrode material having a structure in which layers in which lithium ions are present and layers in which transition metal ions are present are arranged alternately. For example, LiCoO2, LiNi 0.5 Mn 0.5 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2 and other Li-containing compounds such as these can be mentioned.

[0027] The precursor of the positive electrode material is not particularly specified, but is a cation composition other than lithium ions of the target positive electrode material. For example, it is a hydroxide or oxide containing Ni, Co, Mn, Al, etc. The precursor may be a mixture of Co compounds such as Co3O4 and Co(OH)2, Ni compounds such as NiO and Ni(OH)2, Mn compounds such as MnO, MnO2, Mn3O4, MnOOH, and Mn(OH)2, and Al compounds such as Al2O3 and Al(OH)3, which are blended so that the compounds of individual elements have the composition of the target positive electrode material.

[0028] The lithium salt is a substance containing Li and is a substance that can be a raw material for the positive electrode material of the lithium ion secondary battery. Although not particularly specified, for example, lithium hydroxide, lithium carbonate, etc. can be mentioned.

[0029] (Composite Oxide) The composite oxide constituting the additive for the positive electrode material of the lithium-ion secondary battery of the present invention has a composition formula of M x Zr 1-x O 2-y and is a single-phase carbide containing two or more kinds of cations, specifically Zr and M. M is one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y, and satisfies 0 < x < 1 and 0 < y < 1.5. Specific examples include Y 0.28 Zr 0.72 O 1.86 、Y 0.33 Zr 0.67 O 1.84 、Y 0.15 La 0.15 Zr 0.7 O 1.85 and the like.

[0030] M is preferably any one or more elements selected from Gd, Y, and Sc. By selecting these elements, the reaction with the Li source and the precursor proceeds more easily, and a more crystalline positive electrode material can be obtained.

[0031] Alternatively, M is preferably two or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y. By selecting two or more elements, the reaction with the Li source and the precursor proceeds more easily, and a more crystalline positive electrode material can be obtained.

[0032] (X-ray diffraction peak) The composite oxide constituting the additive for the positive electrode material of the lithium-ion secondary battery of the present invention has a half-value width of the diffraction peak appearing at 2θ = 30 ± 1° of 1° or more in the X-ray diffraction using a CuKα ray source. The half-value width of the diffraction peak appearing at 2θ = 30 ± 1° being 1° or more means that the crystallinity of the composite oxide is low.

[0033] In general, when a lithium-ion secondary battery is charged and discharged, lithium ions enter and leave the positive electrode material at the positive electrode. At this time, if the positive electrode material of a lithium-ion secondary battery having a layered structure has high crystallinity, the movement of lithium ions during charging and discharging becomes easier, and improvement in rate characteristics can be expected. In addition, the higher the crystallinity of the positive electrode material, the more the collapse of the crystal structure due to charging and discharging is suppressed, and the less likely it is to deteriorate even when repeatedly charged and discharged. Therefore, the higher the crystallinity of the positive electrode material, the better the characteristics of the lithium-ion secondary battery.

[0034] When preparing a positive electrode material by reacting a precursor of the positive electrode material with a lithium salt, the higher the reactivity of the additive added during the reaction, the more the reaction between the precursor and the lithium salt is promoted, and as a result, a positive electrode material with high crystallinity and a sufficiently developed crystal structure is synthesized. If the crystallinity of the composite oxide constituting the additive is low, the crystal becomes unstable, and the reactivity is improved. Therefore, by using an additive with a large half-width of the diffraction peak appearing at 2θ=30±1°, a highly crystalline positive electrode material can be obtained. The crystallinity of the positive electrode material can be judged from the half-width of the 003 plane diffraction peak appearing around 2θ=18-20° in the X-ray diffraction of a CuKα radiation source. The smaller the half-width of this peak, the higher the crystallinity of the positive electrode material.

[0035] From the viewpoint of reactivity, in X-ray diffraction of the composite oxide using a CuKα radiation source, the half-width of the diffraction peak appearing at 2θ=30±1° is preferably large, and is preferably 2° or more, more preferably 3° or more, 4° or more, or even more preferably 5° or more.

[0036] (specific surface area) The additive for the positive electrode material of the lithium ion secondary battery of the present invention has a specific surface area of ​​50 m 2 / g or more. 2 By making the specific surface area 60 m or more, the reaction with the Li source or precursor proceeds more easily, and a lithium ion secondary battery positive electrode material with better crystallinity can be obtained. 2 / g or more is more preferable, and 70m 2 / g or more, 80m2 / g or more, 90m 2 / g or more, 100m 2 / g or more is more preferable.

[0037] As a pretreatment, the specific surface area is measured by placing approximately 0.3 g of the sample in a flask-type sample cell, degassing it for 40 minutes at 370 °C under a nitrogen gas flow using a FloVac degassing apparatus (manufactured by Anton Paar Japan), and then measuring the surface area using the BET method (single-point method) by nitrogen gas adsorption using a surface area measuring apparatus (NOVAtouch NX-4LX-1, manufactured by Anton Paar Japan).

[0038] <Lithium-ion secondary battery cathode material> The lithium ion secondary battery positive electrode material additive described above can be used to manufacture a lithium ion secondary battery positive electrode material. Specifically, for example, lithium carbonate and a transition metal composite compound are adjusted so that the positive electrode material has a desired chemical composition, and the additive for the lithium ion secondary battery positive electrode material of the present invention is added to the lithium transition metal composite oxide, which is the positive electrode material, in a ratio of 0.5 mass %, and then dry mixed with a precision mixer. Then, the temperature is raised to 850°C at 10°C / min in an air atmosphere, whereby a positive electrode material having a layered structure can be synthesized. As the additive, two or more types of the additive for the lithium ion secondary battery positive electrode material of the present invention may be used. By using two or more types of additives, the diffraction peak of the 003 plane of the manufactured positive electrode material becomes larger and sharper. That is, the crystallinity of the positive electrode material becomes higher. Note that the manufacturing method of the lithium ion secondary battery positive electrode material is not limited to this.

[0039] <<Method for producing additives for positive electrode materials of lithium-ion secondary batteries>> Next, a method for producing the additive for a positive electrode material of a lithium ion secondary battery according to the present invention will be described.

[0040] The additive for a positive electrode material of a lithium ion secondary battery of the present invention can be produced, for example, by mixing raw materials by a wet method and baking the mixture. (1) A step of dissolving a raw material of a composite oxide of an additive for a positive electrode material of a lithium ion secondary battery in water to prepare a raw material aqueous solution; (2) precipitating the raw material aqueous solution; (3) maturing the solution containing the precipitate; (4) washing the precipitate; (5) drying the precipitate to obtain a powder; (6) firing the powder at 400° C. or more and 800° C. or less; The present invention can be produced by a production method having the steps of:

[0041] For mixing the raw materials, in addition to the wet method, for example, a dry method, a spray pyrolysis method, or a CVD method can be used.

[0042] Hereinafter, a method for producing an additive for a positive electrode material of a lithium ion secondary battery, in which raw materials are mixed and fired by a wet method, will be described.

[0043] <Adjustment of raw material aqueous solution> First, the raw material of the composite oxide constituting the additive is dissolved in water to prepare a raw material aqueous solution. As the raw material, for example, zirconium oxychloride and chlorides of one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y, which are cations other than zirconium, can be used. By dissolving these raw materials in water and mixing, an acidic raw material aqueous solution can be obtained. The method of dissolving and mixing is not particularly limited.

[0044] <Precipitation> Next, the raw material aqueous solution is mixed with a basic solution to obtain a precipitate (slurry) by coprecipitating a precipitate consisting of hydroxides of zirconium and one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y, which are raw materials for the composite oxide. At this time, it is preferable to heat the slurry at 70 to 90° C. The heating means is not particularly limited.

[0045] <Solution maturation> The obtained slurry is aged for 4 to 10 hours while being kept at 70 to 90° C. During aging, it is preferable to simultaneously carry out an industrially commonly performed stirring operation such as stirring with a stirring blade or circulation with a pump.

[0046] <Washing of precipitate> The slurry after aging is subjected to a solid-liquid separation operation and a washing operation. There is no particular limitation on the means of the solid-liquid separation operation, and industrially used equipment such as a centrifugal separator and a filter can be used. The washing operation is an operation for reducing chloride ions from a hydroxide slurry containing zirconium and other cations, which is the raw material for the composite oxide, and is carried out, for example, by dispersing the hydroxide in pure water and then using a centrifugal separator and a filter. This washing operation is preferably continued until the content of chloride ions in the hydroxide becomes 3% or less by mass ratio.

[0047] <Drying of the precipitate> The washed hydroxide containing zirconium and other cations is then dried, preferably at a drying temperature of about 400 to 600° C. using an industrially used external heat or internal combustion drying device.

[0048] <Caking the precipitate> The drying operation is followed by a calcination operation. The calcination temperature is preferably 500 to 800°C. The drying operation and the calcination operation can be performed as independent operations, or as a series of continuous operations. The calcination operation dehydrates the hydroxide containing zirconium and other cations, which are the raw materials of the composite oxide, and turns them into a composite oxide. The composite oxide thus obtained may be pulverized as necessary to adjust the particle size. The pulverization may be performed using an industrially used mill, such as a stamp mill, a roller mill, a jet mill, or a ball mill, as long as it can be adjusted to the desired particle size. EXAMPLES

[0049] <Example 1> The chemical formula of the additive is Y 0.3 Zr 0.7 O 1.85The yttrium chloride and zirconium oxychloride adjusted to the above were dissolved in water and mixed, and a precipitate consisting of yttrium-zirconium hydroxide was coprecipitated to obtain a slurry. The obtained slurry was aged at 80°C for 6 hours, and then the slurry was subjected to a filtering-washing operation five times using a filtering device to obtain a cake of yttrium-zirconium composite hydroxide. The obtained composite hydroxide cake was placed in a sagger and dried at 500°C for 10 hours, and then fired in a crucible at 600°C for 10 hours to obtain a composite oxide. The obtained composite oxide was pulverized with a jet mill to obtain a composite oxide additive for a lithium ion secondary battery positive electrode material.

[0050] <Examples 2 to 5> In Examples 2 to 5, Y 0.3 Zr 0.7 O 1.85 A composite oxide additive for a lithium ion secondary battery positive electrode material was produced under the same conditions as in Invention Example 1, except that a chloride was used instead of the above to adjust the additive to have the chemical formula shown in Table 1. In Invention Example 5, a composite oxide additive for a lithium ion secondary battery positive electrode material was produced under the same conditions as in Invention Example 1, except that a chloride was used to adjust the slurry to have the chemical formula shown in Table 1, and firing in a crucible was performed at 650°C.

[0051] <Comparative Examples 1 to 3> In Comparative Examples 1 to 3, the additives were adjusted using chlorides so that they had the chemical formulas shown in Table 1, and calcination in a crucible was carried out at 1000°C. Except for this, composite oxide additives for lithium ion secondary battery positive electrode materials were prepared under the same conditions as in Invention Example 1.

[0052] (X-ray diffraction peak) The composite oxide additive for lithium-ion secondary battery positive electrode material prepared was evaluated by X-ray diffraction. A sample of the composite oxide additive for lithium-ion secondary battery positive electrode material was placed in a sample holder, and X-ray diffraction measurements were performed using a Rigaku desktop X-ray diffractometer MiniFlex600 (CuKα radiation source) under conditions of 20 to 80°, step of 0.02°, and 5° / min. From the obtained X-ray diffraction pattern, the half-width of the diffraction peak that appeared at 2θ=30±1° was calculated.

[0053] <<Preparation of positive electrode material>> The chemical formula of the positive electrode material is Li 1.05 Ni 0.5 Co 0.20 Mn 0.3 O2, lithium carbonate, transition metal complex compound (Ni 0.5 Co 0.2 Mn 0.3 The additives produced in Examples 1 to 5 and Comparative Examples 1 to 3 were added at a ratio of 0.5 mass % to the lithium transition metal composite oxide constituting the positive electrode material, and the mixture was dry-mixed in a precision mixer. Thereafter, the temperature was raised to 850° C. at a rate of 10° C. / min in an air atmosphere to synthesize lithium ion secondary battery positive electrode materials having a layered structure.

[0054] The lithium-ion secondary battery positive electrode materials with eight types of layered structures were evaluated by X-ray diffraction. A sample of the lithium-ion secondary battery positive electrode material was placed in a sample holder, and X-ray diffraction measurements were performed using a Rigaku desktop X-ray diffractometer MiniFlex600 (CuKα source) under conditions of 10 to 100°, step of 0.02°, and 3° / min. From the obtained X-ray diffraction pattern, the half-width of the diffraction peak that appeared around 2θ = 18 to 20° was calculated.

[0055] Table 1 shows the composition of the obtained composite oxide additive for lithium ion secondary battery positive electrode material, the half-width of the X-ray diffraction peak appearing at 2θ=30±1° in X-ray diffraction from a CuKα radiation source, and the half-width of the X-ray diffraction peak appearing near 2θ=18 to 20° of the lithium ion secondary battery positive electrode material produced using the same. In this example, if the half-width of the X-ray diffraction peak appearing near 2θ=18 to 20° is 0.223° or less, the crystallinity of the lithium ion secondary battery positive electrode material was determined to be high.

[0056] [Table 1]

[0057] Examples 1 to 5 of the present invention are the composite oxide additive for the lithium ion secondary battery cathode material of the present invention, and the lithium ion secondary battery cathode material produced using the same. As shown in Table 1, Examples 1 to 5 of the present invention had low crystallinity, with the half-width of the diffraction peak appearing at 2θ=30±1° being 1° or more in the X-ray diffraction of a CuKα radiation source. The lithium ion secondary battery cathode material produced using these had a half-width of the X-ray diffraction peak appearing near 2θ=18 to 20° being 0.223° or less, and it was confirmed that it had high crystallinity. In other words, it was confirmed that the composite oxide additive for the lithium ion secondary battery cathode material of the present invention promotes crystal growth during the synthesis of the cathode material.

[0058] The composite oxide additives for lithium ion secondary battery positive electrode material of Comparative Examples 1 to 3 have compositions within the range of the present invention. However, because the calcination temperature was high, the crystallinity of the additives was high, and the half-width of the diffraction peak appearing at 2θ=30±1° in the X-ray diffraction of a CuKα radiation source was less than 1°. The lithium ion secondary battery positive electrode material manufactured using these had a half-width of the X-ray diffraction peak appearing around 2θ=18 to 20° in the X-ray diffraction of a CuKα radiation source of more than 0.223°, and had low crystallinity.

Claims

1. An additive made of a composite oxide that is added in a process of producing a positive electrode material for a lithium ion secondary battery by reacting a precursor of the positive electrode material with a lithium salt, The composition formula of the composite oxide is M x Zr 1-x O 2-y and M is one or more elements selected from La, Sc, Sm, Nd, Gd, Yb, and Y; 0<x<1 and 0<y<1.5 are satisfied, In the X-ray diffraction of the composite oxide using a CuKα radiation source, the half-width of the diffraction peak appearing at 2θ=30±1° is 1° or more.

1. An additive for a positive electrode material of a lithium ion secondary battery.

2. Specific surface area is 50m 2 2. The additive for a positive electrode material of a lithium ion secondary battery according to claim 1, wherein the additive has a molecular weight of at least 1.0 mg / g.

3. 2. The additive for a positive electrode material of a lithium ion secondary battery according to claim 1, wherein the M is at least one element selected from the group consisting of Gd, Y, and Sc.

4. 2. The additive for a positive electrode material of a lithium ion secondary battery according to claim 1, wherein M is two or more elements selected from the group consisting of La, Sc, Sm, Nd, Gd, Yb, and Y.

5. A lithium ion secondary battery positive electrode material using the additive for lithium ion secondary battery positive electrode material according to any one of claims 1 to 4, characterized in that in X-ray diffraction using a CuKα ray source, the half-width of an X-ray diffraction peak appearing in the vicinity of 2θ = 18 to 20° is 0.223° or less.

6. A lithium ion secondary battery positive electrode material using two or more kinds of the additive for a lithium ion secondary battery positive electrode material according to any one of claims 1 to 4, wherein in X-ray diffraction using a CuKα radiation source, the half-width of an X-ray diffraction peak appearing in the vicinity of 2θ = 18 to 20° is 0.223° or less.

7. The additive for a positive electrode material of a lithium ion secondary battery according to any one of claims 1 to 4, comprising: A method for producing an additive for a positive electrode material of a lithium ion secondary battery, comprising the step of firing a powder of a composite oxide raw material of the additive for a positive electrode material of a lithium ion secondary battery at 400° C. or more and 800° C. or less.

8. The powder, which is a raw material for a composite oxide used as an additive for a positive electrode material of a lithium ion secondary battery, is (1) A step of dissolving a raw material of a composite oxide of an additive for a lithium ion secondary battery positive electrode material in water to prepare a raw material aqueous solution; (2) A step of precipitating a precipitate from the raw material aqueous solution; (3) maturing the solution containing the precipitate; (4) washing the precipitate; (5) drying the precipitate The method for producing the additive for a positive electrode material of a lithium ion secondary battery according to claim 7, characterized in that it is produced by a method comprising the steps of:

Citation Information

Patent Citations

  • Manufacture of lithium secondary battery positive electrode material

    JP1999354121A

  • Positive electrode active material for lithium secondary battery, manufacturing method thereof and lithium secondary battery

    JP2013182757A

  • A positive electrode active material, a lithium secondary battery containing the same for impurity or swelling control, and a method for manufacturing a positive electrode active material with improved productivity.

    JP2015503181A

  • Positive electrode active material, method for producing the same, and lithium secondary battery including the same

    JP2016506032A

  • Lithium ion secondary battery and positive electrode active material for the lithium ion secondary battery

    JP2018055808A